2008
DOI: 10.1007/s10457-008-9118-5
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of irrigation and intense shade on productivity of alley-cropped tall fescue herbage

Abstract: The relative effects of irradiance and soil water on alley-cropped herbage are poorly understood. Our objective was to determine effects of irrigation on herbage productivity when tall fescue [Lolium arundinaceum (Schreb.) Darbysh.] was grown in two sites, a meadow and a loblolly pine (Pinus taeda L.) alley (620 trees ha -1 ), near Booneville, Arkansas. Three tall fescue entries were space planted in the meadow and pine alley with or without irrigation. Herbage mass and nutritive value were determined at 8-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…However, water and nutrient are sufficient for agriculture in this area because the soil water completely depends on irrigation, and fertilizers are added at the same time. But in agroforestry systems in this area, irrigation generally fails to improve herbage productivity under intense shade of tree, because photosynthetically active radiation (PAR, 400-700 nm wavelength) is a limiting factor (Burner and Belesky 2008) according to the Sprengel-Liebig Law of the Minimum (van der Ploeg et al 1999). Previous studies also showed that when plant growth is not limited by water and nutrients, production is limited by the amount of radiant energy that the foliage can intercept (Monteith et al 1991;Monteith 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, water and nutrient are sufficient for agriculture in this area because the soil water completely depends on irrigation, and fertilizers are added at the same time. But in agroforestry systems in this area, irrigation generally fails to improve herbage productivity under intense shade of tree, because photosynthetically active radiation (PAR, 400-700 nm wavelength) is a limiting factor (Burner and Belesky 2008) according to the Sprengel-Liebig Law of the Minimum (van der Ploeg et al 1999). Previous studies also showed that when plant growth is not limited by water and nutrients, production is limited by the amount of radiant energy that the foliage can intercept (Monteith et al 1991;Monteith 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Besides that effect, the availability of seeds in the soil did not show any constraints. In contrast with tall fescue plants showing declining flowering under evergreen pines (Burner and Belesky 2008), tall fescue plants under deciduous poplars may not compromise the reposition of seeds in the soil bank.…”
Section: Discussionmentioning
confidence: 86%
“…Grass tillering is usually reduced because the tree canopy decreases the ratio of red/far red light (R:FR) reaching the understory (Casal et al 1987). C 3 grasses' tillering is reduced under pines, poplars or oaks when compared with open pastures (Burner and Belesky 2008;Pincemin et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After trees have become established, it is more likely that growth in the understory will be limited by reduced solar irradiation. Burner and Belesky [5] found that solar irradiation limited the productivity of tall fescue (Lolium arundinaceum Schreb.) growing in the understory of loblolly pines (Pinus taeda L.) planted at 620 tree per ha.…”
Section: Introductionmentioning
confidence: 99%